Effect of water-saving irrigation on the seasonal emission of CH4 from paddy field - PENG Shi-zhang; LI Dao-xi; JIAO Xi-yun; HE Yan; YU Jin-yuan (浙江大学学报. 农业与生命科学版)
Based on water-saving irrigation technique and observation in situ with closed static chamber technique, the effect of rice water-saving controlled irrigation on the seasonal emission law of CH4 from paddy field was investigated. The results show that the seasonal variation of CH4 emission from paddy field under controlled irrigation (PFCI) takes on distinct one-peak pattern, occurring at the initial tillering stage of rice. The total CH4 emission from PFCI was 24.43 g·m-2, the seasonal average of CH4 emission rate was 7.95 mg·m-2·h-1, reduced by 39% compared with that from paddy field under flooding irrigation (PFFI). There is no statistically significant difference on the mean emission rates of CH4 between two kinds of irrigation patterns during the ponding to the peak tillering stage of rice (0.05<P=0.87); while CH4 emission rate from PFCI is significantly lower than that from PFFI during the later tillering to ripening stage of rice (0.00=P<0.05). July is the most month of CH4 emission in the whole rice growth season in rice production areas of East China, while the amount of CH4 emission from PFCI changes greatly among various months. In addition, under controlled irrigation, no-water-layer status lower than saturated soil moisture can remarkably reduce CH4 emission from paddy field from the later tillering stage of rice onwards, and the reduction cannot be weakened due to the precipitation and the amendment of nitrogenous fertilizers. Furthermore, the PFCI possibly becomes one of the sinks absorbing the atmosphere CH4.